(3GdbGOI GdLOO JMhjd af GdbjGOI GdEOGQjI Edi Yde fJGFLs - (3LhdeGf(B, (3OGfjGds; (3Cfj eGcjs; (3HhjGJRjSs ((3GdQjGVs (3OGQ GdeQjNs, 2004)
(3aj gPG GdcJGH (B: (3ebOeI GdeJQLejf(B-(3ebOeI GdeDdajf(B-(3GdLRA GdChd (B: (3bhI GdPcGA GdYGWaj (B: (3GdaUd GdChd (B: (3GdbjGOI GdCSGSjI (B: (3GdHYO GdCSGSj (B: (3GdOGFQI GdeaJhMI (B: (3GdaUd GdKGfj YTQ (B: (3GdbjGOI GdeJfGZeI (B: (3GdbGFO GdeTGcS (B((3GdeJfGaQ(B) : (3CfhGY GdJfGaQ (B: (3GdaUd GdKGdK (B: (3GdJTQjM GdYUHj ddbjGOI (B: (3caGAGJ GdPcGA GdGUWfGYj (B: (3GdbGOI GdLjd GdbGOe (B: (3GdaUd GdQGHY (B: (3eLehYI CfeGW hegGQGJ GdbjGOI (B: (3GdbGFO Ph GdHUjQI (B((3Gdedge(B) : (3Ph GdHUjQI jMOK JLGhHG hUOi (B: (3GdaUd GdNGeS (B: (3GdCfeGW GdeJfGaQI JWHb HMPQ (B: (3GdGbJUGO aj GSJNOGe GdefXe (B: (3GdefXe hVGHW GdEjbGY GdaYGd (B((3GdechfGJ(B)-(3GdLRA GdKGfj (B: (3UfYI GdbGOI (B: (3GdaUd GdSGOS (B: (3cja JUHM bGFOG eJLGhHG (B((3GdGcJTGaGJ GdNeSI(B) : (3OGA GdQFjS GdJfajPj (B: (3gd HEecGf cd hGMO Cf jchf CaVd ef GdeJhSW ? (B: (3GdaUd GdSGHY (B: (3GdOhGaYjI fMh GdJZjjQ (B: (3GdGcJTGa GdChd (B: (3GdPGJ GdeKGdjI MjK jHOC GdJZjjQ (B: (3GdGcJTGa GdKGfj (B: (3PGJc GdMbjbjI, Ce gd CfJ JabO GdEMSGS (B: (3GdaUd GdKGef (B: (3GdJMhd, JYRjR GdJZjjQ aj GdbjGOI(B-(3GdLRA GdKGdK (B: (3HfGA JfXjeGJ PGJ PcGA YGWaj (B: (3GdaUd GdJGSY (B: (3GdhGbY GdYGWaj ddaQb (B: (3GdaUd GdYGTQ (B: (3GdhGbY hGdQDjI GdeKGdjI, HK QhM GdMjGI aj eSJbHd GdJfXje (B: (3GdaUd GdMGOj YTQ (B: (3Ndb GdJZjjQ GdeSJOGe(B.s
Keywords: (3GdbGOI GdEOGQjhfs; (3GdbjGOI GdGOGQjIs